Power Control Strategy of Microgrid Based on Adaptive Virtual Impedance - JIA Yaoqin; HU Changhua; HE Qiaohui (Kongzhi Yu Xinxi Jishu)
In order to balance the load power sharing, adding virtual impedance is a simple and effective way. It proposed a new control method based on multiple second-order generalized integrator (MSOGI) harmonic detection and adaptive virtual impedance, which can dynamically adjust the virtual impedances of positive sequence fundamental, negative sequence fundamental and typical frequency harmonics by injecting frequency disturbance and integrating the deviation of active power. Simulation and experimental results show that the reactive power, harmonic power and unbalanced power between DG units can be equally shared even if the line impedance is unknown.